1999
DOI: 10.1007/s004250050610
|View full text |Cite
|
Sign up to set email alerts
|

Gravitropism of hypocotyls of wild-type and starch-deficient Arabidopsis seedlings in spaceflight studies

Abstract: The major purpose of this spaceflight project was to investigate the starch-statolith hypothesis for gravity perception, and a secondary goal was to study plant growth and development under spaceflight conditions. This research was based on our ground studies of gravity perception in the wild type and three starch-deficient (one starchless and two reduced starch) mutants of Arabidopsis thaliana (L.) Heynh. Dark-grown seedlings that developed in microgravity were given one of several (30 min, 60 min, or 90 min)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 23 publications
3
36
2
Order By: Relevance
“…If flavonoid expression is under the same light control in maize seedlings as in Arabidopsis seedlings (Wade et al, 2001;Muller et al, 2005), their dark-grown seedlings may mimic our tt4 mutants with an absence of flavonoid synthesis. This complex role of ethylene, with both stimulatory and inhibitory effects on root gravitropism, may explain the contradictory conclusions in the literature on the question of whether ethylene regulates gravitropism (Wheeler and Salisbury, 1981;Kaufman et al, 1985;Harrison and Pickard, 1986;Wheeler et al, 1986;Lee et al, 1990;Woltering, 1991;Kiss et al, 1999;Madlung et al, 1999). Because both ethylene and flavonoid synthesis are regulated by light, nutrients, and other environmental signals (WinkelShirley, 2002;Vandenbussche et al, 2003), it is likely that these contradictory results come from studies in which the synthesis of these molecules is differentially regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If flavonoid expression is under the same light control in maize seedlings as in Arabidopsis seedlings (Wade et al, 2001;Muller et al, 2005), their dark-grown seedlings may mimic our tt4 mutants with an absence of flavonoid synthesis. This complex role of ethylene, with both stimulatory and inhibitory effects on root gravitropism, may explain the contradictory conclusions in the literature on the question of whether ethylene regulates gravitropism (Wheeler and Salisbury, 1981;Kaufman et al, 1985;Harrison and Pickard, 1986;Wheeler et al, 1986;Lee et al, 1990;Woltering, 1991;Kiss et al, 1999;Madlung et al, 1999). Because both ethylene and flavonoid synthesis are regulated by light, nutrients, and other environmental signals (WinkelShirley, 2002;Vandenbussche et al, 2003), it is likely that these contradictory results come from studies in which the synthesis of these molecules is differentially regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous applications of ethylene gas or the ethylene precursor 1-aminocyclopropane carboxylic acid (ACC) were used to test the role of ethylene in gravitropic responses in a range of species, with contradictory results. In some experiments, ethylene treatment clearly reduced gravitropic responses (Wheeler and Salisbury, 1981;Wheeler et al, 1986;Lee et al, 1990;Kiss et al, 1999;Madlung et al, 1999), whereas others showed no effects (Kaufman et al, 1985;Harrison and Pickard, 1986;Woltering, 1991). A recent study indicated that ethylene increased gravitropic curvature in etiolated maize (Zea mays) roots under conditions where ethylene inhibited elongation (Chang et al, 2004).…”
mentioning
confidence: 99%
“…S4). Long-term (hours to days) morphological responses of plants under hypergravity or mg conditions have been described using plants grown in a centrifuge (Fitzelle and Kiss, 2001;Matsumoto et al, 2010) or aboard the space shuttle/station (Kiss et al, 1999(Kiss et al, , 2012Paul et al, 2012;Roux, 2012), respectively. Such reports indicate that plants can respond with alterations in growth and development to a variety of gravitational accelerations.…”
Section: Results [Ca 2+ ] C Increases Genuinely Induced By Gravistimumentioning
confidence: 99%
“…3B), suggesting that these plants could only generate a gravitropic [Ca 2+ ] c when displaced from their vertical orientation by rotation. Yet, previous research has shown that Arabidopsis seedlings, geminated and grown in space, showed little gravitropic growth under continuous mg conditions (Kiss et al, 1999), whereas continuous hypergravity conditions, applied parallel to their growth axis, caused morphological changes (e.g. alterations in hypocotyl length and diameter; Matsumoto et al, 2010).…”
Section: Relationship Between the Amplitude Of The Sustained [Ca 2+ ]mentioning
confidence: 99%
“…In fact, some older facilities, such as the Biorack on the space shuttle, have shown the utility of a 1-g in-flight control to distinguish deleterious environmental effects of spaceflight from microgravity such as the build-up of ethylene gas (Fig. 1) [11]. To account for these secondary (or indirect) spaceflight effects, the use of 1-g in-flight controls can be implemented.…”
Section: Importance Of Controls In Space Experimentsmentioning
confidence: 99%